Acetoacetyl-CoA transferase ydiF regulates the biofilm formation of avian pathogenic Escherichia coli. (31st December 2022) - Gu, Yi; Lu, Huiqi; Shao, Ying; Fu, Dandan; Wu, Jianmei; Hu, Jiangang; Tu, Jian; Song, Xiangjun; Qi, Kezong
Abstract: Avian pathogenic Escherichia coli (APEC) causes persistent infection of poultry and multi-system diseases, which seriously endanger the development of the poultry industry. Biofilm allows bacteria to adapt to the natural environment and plays an important role in resistance to the external environment and the pathogenicity of APEC, but the mechanism of its formation and regulatory network have not been clarified. In this study, we used a Tn5 transposon random mutation library constructed with APEC and identified ydiF, a gene that has not previously been recognized in E. coli biofilm formation. To confirm that the ydiF gene really can regulate the formation of APEC biofilm, the ydiF gene deletion strain was constructed using APEC81. Protein association networks prediction results show that ydiF is mainly associated with genes related to the metabolism of sugars and fatty acids. Deletion of the ydiF gene significantly reduces the formation of APEC biofilm and scanning electron microscopy indicated that the degree of adhesion between the bacteria was also reduced. The deletion of the ydiF gene also significantly reduced the motility of APEC81 and through transmission electron microscopy APEC81 was observed to have significantly fewer flagella. However, the colony morphology of APEC81 on Congo red and Coomassie brilliant blue media was unaffected. The results of fluorescence quantification showed that the deletion of the ydiF gene caused a down-regulation in the transcription of genes related to the second messenger, sugar metabolism, and quorum sensing. These results indicate that ydiF plays an important role in biofilm formation and the movement of APEC. In addition, it may be possible to regulate the formation of APEC biofilms by different methods such as by regulating the second messenger and metabolic system. Highlights: Screened the novel gene related to APEC biofilm formation ydiF used a mutant library. This study had proved the importance of ydiF gene in the formation of APEC biofilm. This study confirmed that ydiF affects the motility of bacteria, and regulated the transcription of genes related to the second messenger, sugar metabolism, and quorum sensing.